2020
DOI: 10.1016/j.heliyon.2020.e03170
|View full text |Cite
|
Sign up to set email alerts
|

Ligninolytic enzymes and its mechanisms for degradation of lignocellulosic waste in environment

Abstract: Ligninolytic enzymes play a key role in degradation and detoxification of lignocellulosic waste in environment. The major ligninolytic enzymes are laccase, lignin peroxidase, manganese peroxidase, and versatile peroxidase. The activities of these enzymes are enhanced by various mediators as well as some other enzymes (feruloyl esterase, aryl-alcohol oxidase, quinone reductases, lipases, catechol 2, 3-dioxygenase) to facilitate the process for degradation and detoxification of lignocellulosic waste in environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
196
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(199 citation statements)
references
References 161 publications
(175 reference statements)
2
196
0
1
Order By: Relevance
“…Laccases play a vital role in the depolymerization of lignin and its derivatives for delignification (Kumar and Chandra 2020). In this study, the laccase-producing S. baltica strain JD0705 was used to biologically delignify the rice husk powder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laccases play a vital role in the depolymerization of lignin and its derivatives for delignification (Kumar and Chandra 2020). In this study, the laccase-producing S. baltica strain JD0705 was used to biologically delignify the rice husk powder.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis result showed that the delignified rice husk powder yielded more fermented sugar than the undelignified biomass. Laccases depolymerize and degrade the lignin molecules by several subsequent mechanisms including the generation of phenoxy radicals, aromatic ring cleavage, alkyl-aryl cleavage, c-oxidation and c-c cleavage (Kumar and Chandra 2020). Laccases are considered as a green tool in various biotechnological processes in the near future (Giardina et al 2010) because of their unique oxidizing mechanism and liberating only water molecules as the by-product (Kumar and Chandra 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ligninolytic peroxidases have extremely low specificity for substrates. While MnP degrades lignin and phenolic compounds by oxidizing the substrate in the presence of H 2 O 2 and Mn 2+ [ 27 ], LiP degrades various xenobiotic compounds by oxidizing substrates that contain H 2 O 2 and veratryl alcohol [ 27 ]. Moreover, these peroxidases are widely applied in the paper industry and environment protection [ 40 ], because they not only degrade lignin but also a wide range of environmental contaminants, such as phenols, polycyclic aromatic hydrocarbons, and aromatic water-pollutants [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the main extracellular ligninolytic enzymes consist of lignin peroxidase (LiP), manganese peroxidase (MnP), and laccase. All these ligninolytic peroxidases are involved in lignin biodegradation [ 27 ]. Studies showed that the peroxidases of white-rot fungi can oxidize the benzene rings of phenols, non-phenolic aromatics, and amino-aromatic compounds into phenol oxides and hydroxyl free radicals via the epoxide ring-opening reactions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%